Peningkatan Kapasitas dan Mutu Produk Batik Berbasis Green Management di Kabupaten Bangkalan - Rusnalasari, Zulidyana Dwi; Ma’ruf, Aminudin; Nilasari, Aprillia; Parastiwi, Arvyana; Mustafidah, A’imatul (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance the capacity and quality of environmentally friendly batik production in Bangkalan Regency through the application of green management-based technology and innovation. Implemented in Paseseh Village, Tanjung Bumi District, from March to August 2025, the program involves the MSME partner Bisma Batik. Using a participatory approach, the activities include the application of energy-efficient lorot machines to accelerate the wax removal process, training in natural dye production using local materials, and training in business management and digital marketing through social media and online marketplaces. The results demonstrate significant improvements in production efficiency, with wax removal time reduced by up to 30% and production capacity increasing two to three times. The partner also successfully implemented a simple accounting system, developed standard operating procedures (SOPs), and activated digital marketing channels to expand market reach. Overall, the program enhanced efficiency, product quality, and competitiveness while promoting green economy principles and sustainable innovation. This initiative contributes to improving artisans’ welfare, strengthening the local economy, and supporting the preservation of environmentally friendly batik practices.